2018
DOI: 10.1108/ijchm-06-2016-0335
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and personal involvement leading to wine consumption

Abstract: Purpose Wine sales are at the highest volumes ever and warrant a robust understanding of consumption behavior. Consequently, this study aims to examine intrinsic motivational factors (e.g. personal attributes) – those that push the consumer toward wine products – and the extrinsic motivational product attributes (e.g. situational attributes) those that draw – or pull – the consumer toward wine products. Design/methodology/approach A model has been tested in which intrinsic and extrinsic motivations interacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 70 publications
(117 reference statements)
0
38
0
1
Order By: Relevance
“…Recent studies have also shown the diversity of this theory's application in wine tourism. For instance, Taylor et al (2018) have analyzed wine purchases and have developed a model where motivations are mediated by personal involvement. Quintal et al (2017) have used push-pull theory and winescape attributes to explain behavioral intentions in Australian wine regions.…”
Section: Push-pull Theorymentioning
confidence: 99%
“…Recent studies have also shown the diversity of this theory's application in wine tourism. For instance, Taylor et al (2018) have analyzed wine purchases and have developed a model where motivations are mediated by personal involvement. Quintal et al (2017) have used push-pull theory and winescape attributes to explain behavioral intentions in Australian wine regions.…”
Section: Push-pull Theorymentioning
confidence: 99%
“…), to social interactions (status symbol, power); extrinsic motivations are the wine attributes (grape variety, origin, alcohol, price, winery brand, taste, aroma/bouquet, medals and awards, food pairing, etc. ; Taylor et al, 2018, p. 707). Ogbeide (2015) adopted the concept of enduring (stable and durable over time) involvement in the Australian wine market while showing that moderate and low involvement represents the majority of the market (58% and 27% of consumers, respectively).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Wine segmentation is often associated with the consumer's involvement (Aurifeille, Quester, Lockshin, & Spawton, 2002) which plays a key role in sparkling wine consumption (Charters et al, 2011; Morton, Rivers, Charters, & Spinks, 2013; Verdonk et al, 2017). Following Taylor, Bing, Reynolds, Davison, and Ruetzler (2018), the involvement is a combination of personal and social motivations that affect wine purchase through a complex interaction of intrinsic and extrinsic motivations. The intrinsic motivations refer to wine knowledge, to hedonic aspects (pleasure, enjoyment, relax, hobby, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drawing on the theoretical framework of the cognitive appraisal theory, this study has contributed to existing literature on several fronts. First, this research has responded to recent calls for more studies to extend hospitality literature with further exploration on psychological factors that predict wine consumption and related behaviors (e.g., Bonn, Cronin, & Cho, 2016;Taylor et al, 2018). While existing wine literature has stressed the influence of product features (e.g., price, packaging, labeling, and bottle closure) on consumer purchase (e.g., N. Barber et al, 2009;Lu et al, 2017), consumers' inner state is also fundamental to understanding wine purchase behavior.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…However, wine purchasing is a rather complex behavior driven by not only product attributes but also individual factors whereby one's perceptions can even shift their evaluations of product attributes. Thus, hospitality and wine researchers have long sought to understand individual factors beyond product attributes to predict wine consumption behavior (Taylor et al, 2018). For example, Bonn, Kim, et al (2016) show that social influence, perceived usefulness, and perceived use significantly determine consumer intentions to purchase wine online.…”
Section: Introductionmentioning
confidence: 99%